LAICE CubeSat mission for gravity wave studies. Issue 7 (1st October 2015) - Westerhoff, John; Earle, Gregory; Bishop, Rebecca; Swenson, Gary R.; Vadas, Sharon; Clemmons, James; Davidson, Ryan; Fanelli, Lucy; Fish, Chad; Garg, Vidur; Ghosh, Alex; Jagannatha, Bindu B.; et al.
Abstract : Highlights: LAICE CubeSat has been designed to address fundamental questions of atmospheric coupling. LAICE will focus on studying the interaction of weather-sourced gravity waves with the MLTI region. LAICE will combine remote and in-situ observations of ion and neutral variations in the MLTI region. Abstract: The Lower Atmosphere/Ionosphere Coupling Experiment (LAICE) CubeSat mission will focus on understanding the interaction of atmospheric gravity waves generated by weather systems in the lower atmosphere with the mesosphere, lower thermosphere, and ionosphere (MLTI). Specifically, LAICE will focus on the energy and momentum delivered by these waves and attempt to connect the wave sources and the wave effects in three widely different altitude ranges, substantially adding to our knowledge of critical coupling processes between disparate atmospheric regions. The LAICE mission consists of a 6U CubeSat with a four-instrument payload. The retarding potential analyzer (RPA) will provide in-situ ion density and temperature measurements. A four-channel photometer will measure density and temperature variations in the mesosphere through observations of O2 (0, 0) Atmospheric band and O2 Herzberg I band airglows. There are two pressure sensors that comprise the Space Pressure Suite (SPS): the Space Neutral Pressure Instrument (SNeuPI) and the LAICE Ionization gauge Neutral Atmosphere Sensor (LINAS). Both will provide neutral density measurements, but SNeuPI is a prototype sensor that will be validated by LINAS. This CubeSat mission, scheduled for launch in early 2016 from the International Space Station, provides a cost-effective approach to measuring low altitude in-situ parameters along with simultaneous imaging that is capable of addressing the fundamental questions of atmospheric gravity wave coupling in the MLTI region.